Regional crime rates and fear of crime: WISIND findings - Mathias Bug; Martin Kroh; Kristina Meier (DIW Economic Bulletin, 2015)
Many people are afraid of falling prey to crime. The present report investigates the extent to which this fear is in line with the actual regional crime rates. This analysis is based on data from a comprehensive database on the fear of crime, combined with police crime statistics (specifically, adjusted crime statistics which factor in the "dark figure" of unreported crime). No evidence was found to support the (occasionally voiced) contention that the fear of falling prey to crime is irrational in many cases and not representative of the actual level of safety within a given region. In fact, our data shows a clear statistical correlation between regional crime rates and the fear of crime, both of which are more pronounced in the north of Germany than in the south, for instance. The inclusion of cybercrime in crime statistics, however, has meant that the former, higher crime rates and greater fear of crime often recordedin urban areas as opposed to rural regions are no longer as pronounced.
Keywords: K14; R19; H56; H79; H80; 330; security; crime; indicator; fear; fear of crime; home affairs; police; inner security; threat; crime statistics; police statistics